P149 Management Algorithm For Pulmonary Embolism (PE) with Right Heart Strain: A Case Series. (19th November 2012) - Smith, V; Tunnicliffe, G; Fiorino, G; Draper, A; Vlahos, I; Shannon, M; Madden, BP
Abstract : Current guidelines state thrombolysis is first line therapy in hypotensive PE patients and may be of benefit in normotensive patients with right heart strain. There is, however, no specific guidance on selecting these patients. In 2010, St George's Hospital, under the guidance of a multidisciplinary team of specialists, initiated an algorithm for the management of patients with massive PE. The aim of this study was to determine whether the algorithm is an effective means of assessing a series of nine patients who received thrombolytic therapy over a two year period. The age range of the patients was 36–81 years, 5 were male.5 patients had identifiable thromboembolic risk factors: pregnancy and protein S deficiency (1), recent lower limb surgery (2), new cancer diagnosis (1) and chronic immobility (1). All 9 patients had a computed tomography pulmonary angiogram (CTPA) confirming large proximal PEs with elevated troponin I and NT-pro-BNP levels at diagnosis. Right heart strain was demonstrated on echocardiogram in five patients with evidence of intracardiac thrombus in two. The remaining patients had right heart strain demonstrated by CTPA. The indications for thrombolysis were cardiac arrest (1), hypotension (1), intracardiac thrombus (2) and significant right ventricular strain(5).There was one mortality within this cohort following retroperitoneal bleed. This patient underwent an echocardiogram 5 days post thrombolysis revealing severely dilated right heart and RVSP of 61mmHg. Patients achieved good resolution of thrombus on repeat CTPA, and no evidence of right heart strain on follow up echocardiogram. The majority of these patients had improved right ventricular function post thrombolysis. This small cohort study demonstrates the variability in the clinical presentations and physiological manifestations of massive PE, hence the need for early specialist input. The algorithm is an effective tool in identifying high mortality risk patients and those likely to develop pulmonary hypertension, thus allowing early specialist review and intervention.